Structural Mimicry of the Dengue Virus Envelope Glycoprotein Revealed by the Crystallographic Study of an Idiotype-Anti-idiotype Fab Complex - Wong, Yee Hwa (AMER SOC MICROBIOLOGY, 2023)
10.1128/JVI.00406-17